Cost-benefit analysis of traditional seismic retrofitting strategies integrated in the renovation of stone masonry buildings - Maio, Rui (2020)
This study discusses the cost-benefit analysis resulting from the application of traditional seismic retrofitting strategies on four case studies considered representative of both rural and urban stone masonry building stock of Faial Island, in Azores (Portugal). The seismic performance-based assessment was carried out by applying the N2 Method procedure, and the global seismic capacity of each case study estimated by using a three-dimensional model based on the macroelement approach, which combines both the in-plane and out-of-plane response of masonry buildings, to perform nonlinear static analyses. Fragility and loss estimation was evaluated according to the HAZUS methodology. In general terms, the cost-benefit analysis has demonstrated that the studied retrofitting strategies are indeed capable of reducing substantially the seismic vulnerability of the considered case studies, and also that they represent, in fact, a limited amount of the total replacement cost, not compromising, therefore, their economic viability.